الاستعمال اللغوي للمفعول المطلق وتطبيقاته في القرآن الكريم : دراسة تأصيلية وتحليلية - محسن، محمد أنس (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2016)
This research aims to highlight the term “Maf'ul Mutlaq” (Cognate Accusative or literally the Absolute Object) which is not bound to any of the prepositions. The "Absolute Effect" (Cognate Accusative) can be divided into four categories; Emphasis for the type of action, the explanation for it, Emphasis on the quantity and emphasis on itself or other that is evident through the findings from Holy Quran that the verbal noun that emphasizes is mentioned in a more frequent manner than the rest and is absolutely undeletable. Through this study, the researcher is trying to focus and determine the effectiveness of the substitute of the cognate accusative in the Quran. The researcher also tries to analyse the factors that contribute to the differences in the opinions of the grammarians on the function of the cognate accusative by attending to all its aspects in this regard. The substitution of the cognate accusative for other grammatical categories, the stylistic representations of it and the purposes of the substitution will also be explained. Thus, a great source like the Quran is the essence of the study as its style, form of expressions and formation are among the most significant Arabic resources; it has been proven that the Quran which is considered is the most authentic source. In this regard, the research is carried out based on the descriptive and analytical method that will look into the evidences and views from the scholars.